2023
DOI: 10.1002/fee.2604
|View full text |Cite
|
Sign up to set email alerts
|

Recognition and completeness: two key metrics for judging the utility of citizen science data

Abstract: Biodiversity citizen science data are being collected at unprecedented scales, and are key for informing conservation and research. Species‐level data typically provide the most valuable information, but recognition of specimens to species level from photographs varies among taxa. We examined a large dataset of Australian photographic observations of terrestrial invertebrates uploaded to iNaturalist to quantify recognition to species across different taxa. We also quantified the proportion of Australian specie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…For groups that are not well represented on photo-sharing websites, community data may need to be supplemented with data from museum specimens to achieve the desired results; for example, Ferro and Flick (2015) found that using only records from BugGuide poorly predicted the distribution of a rove beetle, but when records from museums were included the predicted distribution improved. Alternatively, data users could focus on charismatic groups that have the highest rates of recognition (identification to species level) and representation (% of known species represented in a data set), such as Lepidoptera and Odonata (Mesaglio et al 2023a), which may help account for biases.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For groups that are not well represented on photo-sharing websites, community data may need to be supplemented with data from museum specimens to achieve the desired results; for example, Ferro and Flick (2015) found that using only records from BugGuide poorly predicted the distribution of a rove beetle, but when records from museums were included the predicted distribution improved. Alternatively, data users could focus on charismatic groups that have the highest rates of recognition (identification to species level) and representation (% of known species represented in a data set), such as Lepidoptera and Odonata (Mesaglio et al 2023a), which may help account for biases.…”
Section: Resultsmentioning
confidence: 99%
“…So both across and within websites, these orders are overrepresented compared to their diversity. Mesaglio et al (2023a) reported that Lepidoptera and Odonata were the best recognized and most completely represented terrestrial invertebrate taxa in Australia on iNaturalist. There is also a bias to photograph larger, more colorful species within a given taxon compared to those that are smaller or less colorful, as Braz Sousa et al ( 2022) demonstrated with mosquitoes.…”
Section: Publications and Records Per Taxonmentioning
confidence: 99%
“…However, the rate of plant taxon determination to species level in this study is quite better than what is noted in some taxa of animal kingdom. Indeed [30] found out in Australia that only 60.9% of the taxa are determined to species level in the terrestrial invertebrates' observations on iNaturalist. With respect to plant species of Africa, my suggestion is to refer to the specimen images where possible to complement the determination of species.…”
Section: -Discussion and Conclusionmentioning
confidence: 99%
“…For example, management and policy implications from further investigations of insect responses to fire would benefit from a focus on lower taxonomic levels (Saunders et al, 2021). To this end, further fire‐response research on readily identifiable insect species, from groups including dragonflies, damselflies, and butterflies which are well represented in iNaturalist observations (Mesaglio et al, 2023), would provide finer scale insights more applicable to environmental managers. By integrating the data available through standardized local, species‐, or population‐specific monitoring and broader scale citizen science data, we will have a greater information base from which to identify how and where to sample minimizing gaps and redundancies post‐disturbance.…”
Section: Discussionmentioning
confidence: 99%